KONSTRUKSI OPINI PUBLIK SEKURITISASI TERORISME 9/11 PEMERINTAH AMERIKA SERIKAT MELALUI MEDIA MASSA - Bela Rena, Ni Made Rimas; Putri, Penny Kurnia; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT In the wake of 9/11 attack, public opinion was essential for the securitization process of terrorism in waging war on Afghanistan and Iraq. This research aims to find out the political communication strategy carried out by the U.S. government to manipulate the news agenda to spread its propaganda. By using descriptive qualitative research method, researcher found that media and information management were being used for the sake of media agenda setting to form the expected collective opinion. The importance of maintaining credibility before an international audience became an obstacle to the U.S. government in regulating the circulation of information through mass media with international transmissions, such as CNN. As a result, its political communication strategy was only effective to affect the U.S. citizens. Key Words: Securitisation of terrorism, propaganda, agenda setting, and public opinion.